Exploring the Impact of Psychological Capital and Coworker Support on Happiness at Work: Thriving as a Mediator Among Women Quality of Work Life - Imas Pradnyanita Wistarini, Ni Nyoman; Fajrianthi, Fajrianthi; Hadi, Cholichul (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The factors influencing happiness at work, specifically focusing on Balinese women who balance multiple roles in their personal, community, and professional lives. Happiness at work has become an important topic due to its significant impact on overall well-being, job satisfaction, and organizational success. This research aims to determine the influence of psychological capital and colleague support on happiness at work and thriving as a mediator in Balinese women with multi-roles. The complex roles and demands undertaken by Balinese women cause a high possibility of conflict, which causes absenteeism at work, stress, fatigue, and happiness at work. The characteristics of the subjects in this study were female, domiciled in Bali, part of a banjar manner in a traditional village, married and preferably having at least one child under 14 years of age, working in certain agencies as professionals, and having a minimum of 1 year of service. The sampling techniques used were convenience and snowball sampling. There are four scales used in this research, namely Psychological Capital Questionnaire, Co-worker Support Scale, Thriving at Work Questionnaire, and Happiness at Work Questionnaire. Data analysis in this research uses PLS. The research results show a direct influence between psychological capital and happiness at work and a direct effect between thriving and happiness at work. However, colleague support does not directly influence happiness at work. Then, thriving can act as a variable that mediates the effect of psychological capital on happiness at work and the influence of colleague support on happiness at work.